Religion and the Limits of Women’s Religious Role Identity - Ogege Samuel Omadjohwoefe (JOURNAL OF INNOVATIVE RESEARCH IN MANAGEMENT AND HUMANITIES, 2010)
The paper examines religion and the limits of women’s religious role identity. In every belief system, women are more religiously active than men. Paradoxically, despite their high degree of religiosity, they are relegated to marginal positions in all major religions. The paper maintains that the subordination of women religious status and role is justified and legitimized through patriarchy built in theological mythology. However, women no longer accept the status quo as God given rather they challenge the patriarchal underpinnings of religious traditions. This agitation, no doubt, has yielded positive results as women are now ordained priests and bishops in some religion and many others play the role of Founder, Seers and Prophetesses. The paper recommends that women should not relent in the struggle to erase the subordination and devaluation of women religious role. It is only through that process that they will regain their pride of place in religious and other activities in society.